Da era das barcas à era das pontes : os debates em torno da construção da Ponte do Guaíba / Travessia Régis Bittencourt (1955-1958) - Freitas, Eduardo Pacheco (2017)
This thesis aims to analyze the process of construction of the Guaíba’s Bridge/Travessia Régis Bittencourt, occurred in the 1950s, through the debates that were in its genesis. Thus, in addition to recovering the decision-making process around the work, we rescued as perceptions and representations that circulated about Rio Grande do Sul and its future in that period. Since the 1940s, the large increase in motorized traffic by regional roads led to a congestion of the boat service that crossed the Guaíba, between a city of the same name and a capital Porto Alegre, making it obsolete. In search of a solution, discussions began within the technical field, where divergences regarding the best alternative to the so-called "dry crossing of the Guaíba" arose among the engineers, and also in the political field, where the work was viewed by most agents as fundamental for the progress of Rio Grande do Sul and for a minority as an unnecessary expense. However, since the emergence of the Departamento de Estradas de Rodagem (Daer) in 1938, a policy of replacing bridges of riverboat services across the state had already been set in motion, preamble to one of the largest road engineering works of that period in Brazil, Travessia Régis Bittencourt. To accomplish our goal, we bring in the thesis vast documentation, divided into two types of sources. In the first type, we work with documents produced by Daer, where data and technical discussions help us to better understand not only the achievement of the work, but the relationship between bridge building and progress. As a second source, we use the debates in the Assembleia Legislativa do Estado do Rio Grande do Sul (Alergs), which allow us to better understand the participation of the political field in the process.